2022
DOI: 10.3389/fped.2022.1083370
|View full text |Cite
|
Sign up to set email alerts
|

Expected small left heart size in the presence of congenital diaphragmatic hernia: Fetal values and Z-scores for infants confirmed to have no heart disease postnatally

Abstract: ObjectivesIn fetuses with left-sided congenital diaphragmatic hernia (CDH), left heart structures may appear small, but usually normalize after birth in the absence of structural cardiac anomalies. To decrease the possibility of an erroneous diagnosis of structural heart disease, we identify normal values for left heart structures in the presence of left CDH and secondarily investigate the relationship of left heart size and survival to neonatal hospital discharge.MethodsLeft heart structures [mitral valve (MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A resultant change in cardiac axis and orientation may also create an apparently smaller LV. Nevertheless, postdelivery studies have confirmed that neonates born with CDH had, in fact, a smaller LV [28]. Whether it is a true reduction in size or an “apparently” small ventricle, it most likely reflects continuous mechanic compression or compromised preload secondary to CDH-PH.…”
Section: Discussionmentioning
confidence: 99%
“…A resultant change in cardiac axis and orientation may also create an apparently smaller LV. Nevertheless, postdelivery studies have confirmed that neonates born with CDH had, in fact, a smaller LV [28]. Whether it is a true reduction in size or an “apparently” small ventricle, it most likely reflects continuous mechanic compression or compromised preload secondary to CDH-PH.…”
Section: Discussionmentioning
confidence: 99%